Morphological study of tooth development in podoplanin-deficient mice. - Kenyo Takara; Naoki Maruo; Kyoko Oka; Chiaki Kaji; Yuji Hatakeyama; Naruhiko Sawa; Yukinari Kato; Junro Yamashita; Hiroshi Kojima; Yoshihiko Sawa (PLoS ONE, 2017)
Podoplanin is a mucin-type highly O-glycosylated glycoprotein identified in several somatyic cells: podocytes, alveolar epithelial cells, lymphatic endothelial cells, lymph node stromal fibroblastic reticular cells, osteocytes, odontoblasts, mesothelial cells, glia cells, and others. It has been reported that podoplanin-RhoA interaction induces cytoskeleton relaxation and cell process stretching in fibroblastic cells and osteocytes, and that podoplanin plays a critical role in type I alveolar cell differentiation. It appears that podoplanin plays a number of different roles in contributing to cell functioning and growth by signaling. However, little is known about the functions of podoplanin in the somatic cells of the adult organism because an absence of podoplanin is lethal at birth by the respiratory failure. In this report, we investigated the tooth germ development in podoplanin-knockout mice, and the dentin formation in podoplanin-conditional knockout mice having neural crest-derived cells with deficiency in podoplanin by the Wnt1 promoter and enhancer-driven Cre recombinase: Wnt1-Cre;PdpnΔ/Δmice. In the Wnt1-Cre;PdpnΔ/Δmice, the tooth and alveolar bone showed no morphological abnormalities and grow normally, indicating that podoplanin is not critical in the development of the tooth and bone.